Anastomosis bilio-digestivas muco-mucosas: aspectos técnicos - Parodi, José; Olazábal, Mario; Percovich, C.; Montoya, E; Estellano, F; Estrada, D.; Fernández, G (Cirugía del Uruguay, 1984)
Six animals, half-breed dogs, with an average weight of 18 kg, were used for reimplantation of the chofe• doc;hus, in gyr model inver¡tigation work reportlng biliogig!! stivfl ª"ªstome>sis in this choledochus.